1970
DOI: 10.3126/bibechana.v7i0.4047
|View full text |Cite
|
Sign up to set email alerts
|

Surfactants, its applications and effects on environment

Abstract: Surfactant is being considered as a very demandable molecule in the field of chemistry. This paper reviews most important factors especially the uses of surfactants and their effects on environment. Evaluation of surfactants are based on examining the ability of the surfactant to maintain lower interfacial tension between target contaminant and water, satisfying lower CMCs, and sustaining lower sorption and precipitation to target substrate. Surfactant mixtures of anionic and nonionic surfactant are shown to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Surfactants (Surface Active Agent) also called amphiphilic compounds or tensides due to their specific structure and utility properties (foaming, wetting, softening, antistatic, caking, emulsifying, adsorptive, solubilizing, thermal and chemical stability) are widely used in industry, washing, laundry, cosmetics, pharmaceuticals, textiles, microelectronics, paints, polymers, as well as in food and paper industry, etc. (Atayi et al 2002;Kowalska 2009;Shah et al 2011). The surfactant molecule consists of the non-polar -hydrophobic part (hates water, loves oil) which is usually a long hydrocarbon chain and the polar-hydrophilic part (loves water, hates oil) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactants (Surface Active Agent) also called amphiphilic compounds or tensides due to their specific structure and utility properties (foaming, wetting, softening, antistatic, caking, emulsifying, adsorptive, solubilizing, thermal and chemical stability) are widely used in industry, washing, laundry, cosmetics, pharmaceuticals, textiles, microelectronics, paints, polymers, as well as in food and paper industry, etc. (Atayi et al 2002;Kowalska 2009;Shah et al 2011). The surfactant molecule consists of the non-polar -hydrophobic part (hates water, loves oil) which is usually a long hydrocarbon chain and the polar-hydrophilic part (loves water, hates oil) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that critical micelle concentration increased with addition of methanol and with rise of temperature and decreased with addition of sodium bromide. Shah et al [11] measured the specific conductivity of solutions of cetyltrimethylammonium bromide in absence and in the presence of potassium chloride in methanol-water mixed solvent media containing 0.10, 0.20, 0.30 and 0.40 volume fractions of methanol at 308.15, 318.15 and 323.15 K. The conductance of cetyltrimethylammonium bromide decreased with addition of methanol. It was observed that the conductance of cetyltrimethylammonium bromide increased with increase in concentration as well as with addition of salt (KCl).…”
Section: Electrical Conductivitymentioning
confidence: 99%
“…2 Side effects caused by the surfactants have long been a focus of concern and the application of the surfactants may lead to a series of environmental problems such as water pollution. 3 Therefore, it is particularly necessary to analyze the content of one kind of surfactants for the purpose of the quality assurance of commercial products and for environmental pollution control. Although many methods have been described for the determination of various surfactants in the daily use, there are few methods reported on the detection of surfactants in ooding systems.…”
Section: Introductionmentioning
confidence: 99%